Exploring experienced teachers' attitudes to critical incidents. Issue 1 (2nd January 2022) - Akdağ, Emrah
ABSTRACT: A teacher's professional life comprises several experiences with a pivotal role in shaping the very essence of teaching. Critical Incidents constitute a significant part of these aforementioned experiences of teachers. Within this study conducted at a high-school in Turkey, 17 experienced teachers' critical incidents which left a mark in their professional lives and their attitudes towards these incidents were revealed through Critical Incident Technique developed by Flanagan in 1954. Besides, teachers' current opinions regarding their attitudes at the time of incidents were questioned. This study aimed to explore the difference between the way how teachers acted towards critical incidents and how they would act if they experienced the incidents today. The study also targeted to demonstrate if teacher attitudes undergo a change as they become experienced. This study is expected to contribute to literature concerning teachers' mental lives and to have implications for teachers and other researchers on the field in terms of reflective teaching.